Culture age and carbamoylcholine increase the incorporation of endogenously synthesized linoleic acid in lipids of Trypanosoma cruzi epimastigotes - Villasuso, Ana Laura (2005)
Physiological and cellular adaptations to environmental changes are known to be related to modifications in membrane lipids. This work provides metabolic and compositional evidence that Trypanosoma cruzi epimastigotes are able to synthesize and desaturate fatty acids, to incorporate them into their lipids, and to modify this incorporation when carbamoylcholine is present in the medium. The fatty acids formed from [2-14C]acetate in the period from 2 to 9 days were mostly (70%) incorporated in phospholipids, the remainder 30% being recovered in neutral lipids, such as triacylglycerols (TAG) and diacylglycerols (DAG). The main fatty acids formed from [2-14C]acetate were saturates (16:0, 18:0), monoenes (16:1, 18:1) and dienes (mostly 18:2). The ratios between labelled unsaturated and saturated fatty acids increased continuously with growth, consistent with a precursor–product relationship between the main fatty acids, and with the occurrence in T. cruzi of Δ9- and Δ12-desaturases. From days 2 to 5, [14C]18:2 was the main fatty acid produced. Accordingly, the fatty acid profiles showed a significant increase in the percentage of 18:2 in all lipids in the period under study, especially in the first 2 to 5 days. In the presence of carbamoylcholine, the labelling of DAG and TAG with [14C]18:2 augmented. The results indicate that T cruzi is able to synthesize the main types of fatty acids required to form its membrane lipids, and to exchange them actively in response to environmental stimuli.